Indigenous Peoples’ Experience and Understanding of Menstrual and Gynecological Health in Australia, Canada and New Zealand: A Scoping Review - Donna Ciccia; Aunty Kerrie Doyle; Cecilia H. M. Ng; Mike Armour (International Journal of Environmental Research and Public Health, 2023)
There are a variety of cultural and religious beliefs and customs worldwide related to menstruation, and these often frame discussing periods and any gynecological issues as taboo. While there has been previous research on the impact of these beliefs on menstrual health literacy, this has almost entirely been confined to low- and middle-income countries, with very little information on high-income countries. This project used the Joanna Briggs Institute (JBI) scoping review methodology to systematically map the extent and range of evidence of health literacy of menstruation and gynecological disorders in Indigenous people in the colonized, higher-income countries of Australia, Canada, and New Zealand. PubMed, CINHAL, PsycInfo databases, and the grey literature were searched in March 2022. Five studies from Australia and New Zealand met the inclusion criteria. Only one of the five included studies focused exclusively on menstrual health literacy among the Indigenous population. Despite considerable research on menstrual health globally, studies focusing on understanding the menstrual health practices of the Indigenous populations of Australia, New Zealand, and Canada are severely lacking, and there is little to no information on how Indigenous beliefs of colonized people may differ from the broader society in which they live.